Effect of Fenofibrate as PPARα Agonist in Suppressing the Development of Oxaliplatin-Induced Peripheral Neuropathy via TRPA1 Modulation - Alma Nuril Aliyah; Pingkan Aprilia; Anak Agung Sagung Dyah Pramesti; Tarisya Dinda Saraya; Galuh Laksatrisna Pide; I Nengah Budi Sumartha; Luke Wongso; Samirah; Mahardian Rahmadi; Muhammad Zaki Bin Ramli; Chrismawan Ardianto (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: CIPN (Chemotherapy-induced Peripheral Neuropathy) primarily affects the sensory system and is accompanied by pain, autonomic dysfunction, and motor impairments. Alterations of intracellular second messengers at the supraspinal level in CIPN needed to be explored more. In addition, there is a lack of evidence regarding implications for the supraspinal area through the propagation of pain via the ascending pathway. Objective: In this study, we evaluated the effect of fenofibrate as a PPARα agonist in suppressing the development of CIPN. Methods: Twenty-four mice were distributed to the normal control group, neuropathy group, and neuropathy with the treatment of fenofibrate 75 and 150 mg/kg groups, resulting in 6 animals per group. Oxaliplatin was injected on days 0, 2, 4, and 6. The hot plate test was performed before the oxaliplatin administration and then continued on the 7th, 14th, and 21st days. Thalamus tissues were collected to measure the TRPA1 mRNA expression using qPCR. Results: Fenofibrate 75 mg/kg co-treatment with oxaliplatin tended to prevent the enhancement of oxaliplatin-induced thermal hyperalgesia in hind-paw withdrawal and rubbing responses. Furthermore, fenofibrate 75 and 150 mg/kg co-treatment with oxaliplatin significantly reduced the relative TRPA1 mRNA expression but did not modulate the relative BDNF mRNA expression in the thalamus. Conclusion: PPARα agonist has a potential effect in suppressing the development of CIPN. However, given the various perspectives on the role of neurotrophins in CIPN, additional non-clinical investigations, are needed to provide more insight into other mechanisms of CIPN and the role of PPAR agonists.